Pinjaman Online Menurut Hukum Islam Analisa Penerapannya di Kecamatan Tanjung Pura Kabupaten Langkat - OK Cut Nurul Mahdalena (Journal Smart Law, 2024)
This research aims to find out the law on online loans in Islamic law, find out the views of the people of Tanjung Pura sub-district towards online loans, and to find out the interest of the people of Tanjung Pura towards online loans. This research is descriptive qualitative research. The respondents in this research were STAIJM Tanjung Pura students. Data collection techniques by means of observation, interviews and documentation. Data analysis techniques are data reduction, data presentation and drawing conclusions. The results obtained from the research carried out include: In online loan contracts such as those found in the Akulaku Application, there is one of the rukun requirements that has not been fulfilled, namely the object of the contract where the loan transaction should not contain elements of usury. And in the contract transaction on the application there is an additional price when returning the loan, there is also a loan discount as an approval fee. So, if you look at the terms and conditions in the Akulaku application between muqrid and muqtarid, it does not fulfill the terms of the contract in Islamic law. Because there are pillars in the form of objects being transacted that have not been fulfilled, the loan transaction should be clear and the conditions are not met. According to the perspective of Islamic law, according to the theory used, this online loan is not valid because one of the conditions of harmony has not been fulfilled. The terms of this pillar are related to the object being transacted. Therefore, the additional or accompanying interest from the credit object in this case is categorized as part of usury. Because loan repayment transactions are accompanied by additional costs.